О геттерных свойствах некоторых окислов - Турова А. И. Алла Ивановна; Суровой Э. П. Эдуард Павлович; Зингер Г. В. Григорий Вольфович; Яворов П. Ф. Петр Филиппович (1985, 1985)
Деп. в ОНИИТЭХим г. Черкассы 21.08.85, № 863-ХП-85.